The Use of Financial Spreads As Indicator Variables : Evidence for the U.K. and Germany - Davis, E. (IMF Working Papers; Working Paper, 1994)
There has been growing interest in the use of financial spreads as advance indicators of real activity and inflation. Empirical evidence is marshalled on a range of spreads when these are used in vector autoregressive models of the UK and German economies. It is found that they do have significant information, even after allowing for the effects of other influences upon macro-economic activity.